Role of Maternal Smokeless Tobacco Ingestion During Pregnancy in Delivery of Preterm Babies (Bangladesh Journal of Child Health, 2017)
Background:Smokeless tobacco is an established cause of adverse pregnancy outcome. Preterm deliveries are quite high(14%) in our country and approximately 39% women in Bangladesh use smokeless tobacco (ST).Objective: To determine the outcome of maternal smokeless tobacco ingestion during pregnancy in delivery of preterm babies.Methods: A retrospective case control study was carried out in the department of Pediatrics & department of Obstetrics and Gynecology in Dhaka Medical College Hospital between July 2010 to June 2011. Immediately after admission, detailed history of the newborn baby & mother was taken. A total of 100 cases (preterm babies) and 100 suitably matched controls (sick term neonates) were enrolled. Every case satisfying the selection criteria (inclusion & exclusion criteria) was enrolled in the study. The mother was asked whether she used to use smokeless tobacco (jorda, shada or gul) during pregnancy and about frequency and duration of ingestion of ST.Results: Baseline characteristics of cases and controls were comparable. ST user mothers of preterm babies used ST about 5 times a day. Maternal smokeless tobacco (ST) use during pregnancy was significantly associated (46%) with the delivery of preterm babies (p